2003
DOI: 10.1001/archpsyc.60.7.737
|View full text |Cite
|
Sign up to set email alerts
|

Treating Depression in Alzheimer Disease

Abstract: Sertraline is superior to placebo for the treatment of major depression in Alzheimer disease. Depression reduction is accompanied by lessened behavior disturbance and improved activities of daily living, but not improved cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(101 citation statements)
references
References 67 publications
1
97
0
3
Order By: Relevance
“…[32], [33]]. We used the NPI ratings of the combined 5 mood domains depression/dysphoria, anxiety, irritability/lability, sleep, and appetite (NPI-M) [34,35] and defined the presence of significant behavioural problems as having 2 or more clinically relevant or at least 1 severe mood symptom. Both the CSDD and the NPI are valid, reliable instruments that are widely used to measure ‘behavioural' disturbance in PwD.…”
Section: Methodsmentioning
confidence: 99%
“…[32], [33]]. We used the NPI ratings of the combined 5 mood domains depression/dysphoria, anxiety, irritability/lability, sleep, and appetite (NPI-M) [34,35] and defined the presence of significant behavioural problems as having 2 or more clinically relevant or at least 1 severe mood symptom. Both the CSDD and the NPI are valid, reliable instruments that are widely used to measure ‘behavioural' disturbance in PwD.…”
Section: Methodsmentioning
confidence: 99%
“…The results of previous studies, however, were inconsistent. A clinical trial which targeted AD patients with major depression showed that antidepressant therapy is superior to placebo in treating depression [43]. On the contrary, other trials which targeted depressive AD patients using cutoff scores of depression scales showed that antidepressants are not effective in treating depression [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence to support the use of antidepressants for the treatment of apathy in AD (44) and, in fact, selective serotonin reuptake inhibitors (SSRIs) may increase apathy (45,46). Thus we chose not to consider antidepressants as treatment for apathy in the ADMET study.…”
Section: Issues In Designing a Trial To Test Treatments For Apathymentioning
confidence: 99%